The Influence of Return on Asset (ROA) and Current Ratio (CR) on Firm Value (A Study of Non-Primary Consumer Goods Retail Trade Sub-Sector Companies Listed on the Indonesia Stock Exchange 2021-2024) - Rendi Pauji Mustopa; Ayke Nuraliati; Uswatun Hasanah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to determine the effect of Return On Asset (ROA) and Current Ratio (CR) on firm value. The research employs descriptive and verificative methods with a quantitative approach. The sampling technique used is purposive sampling, resulting in a sample of 14 companies that meet the criteria within the non-primary consumer goods retail trade sub-sector listed on the Indonesia Stock Exchange for the period 2021-2024. The analytical method applied in this study is panel data regression analysis using the Eviews 12 software. The results of the study indicate that Return On Asset (ROA) has no effect on firm value, while the Current Ratio (CR) has a significant effect on firm value.